Maxillary osteomyelitis associated with osteopetrosis: Systematic review - Carvalho, Pedro Henrique de Azambuja [UNESP]; Moura, Lucas Borin [UNESP]; Real Gabrielli, Mario Francisco [UNESP]; Cabrini Gabrielli, Marisa Aparecida [UNESP]; Antonio Pereira Filho, Valfrido [UNESP] (My University, 2018)
Osteopetrosis is a rare condition which presents increased bone density and deficient bone remodeling. The consequential complications include cranial nerve impairment due compression, bone fractures, and osteomyelitis. Maxillary osteomyelitis is uncommon even in osteopetrosis patients. This is a systematic review of the literature regarding the management and outcomes of maxillary osteomyelitis in patients with autosomal dominant osteopetrosis (ADO) type II. A case of this specific pathology is reported. There are 18 cases of maxillary osteomyelitis associated with ADO type II reported in the literature. The mean age of the patients reported was 33.5 (SD 15.9) years, and the male:female ratio was 1:1. Antibiotic therapy was variable, and amoxicillin with clavulanic acid was the main choice (33.33%). Surgery or sequestrectomy was performed in 88.89% of the studies. Complete healing was achieved in only 44.4% of cases. The treatment protocols remain controversial and often do not lead to complete healing. In the case that we report, complete healing was achieved after prolonged antibiotic therapy, hyperbaric oxygen therapy, and partial resection. In conclusion, the management of maxillary osteomyelitis in ADO type II patients is challenging, and complete resolution of the process is dependent on multiple interventions.
Keywords: Maxillary bone; Osteomyelitis; Osteopetrosis; Systematic review